2023
DOI: 10.1002/smll.202305708
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Reprogramming Strategy of Tumor Microenvironment for Rejuvenating Photosensitizers‐Mediated Photodynamic Therapy

Qing Yu,
Xia Li,
Juan Wang
et al.

Abstract: Photodynamic therapy (PDT) has recently been considered a potential tumor therapy due to its time‐space specificity and non‐invasive advantages. PDT can not only directly kill tumor cells by using cytotoxic reactive oxygen species but also induce an anti‐tumor immune response by causing immunogenic cell death of tumor cells. Although it exhibits a promising prospect in treating tumors, there are still many problems to be solved in its practical application. Tumor hypoxia and immunosuppressive microenvironment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 234 publications
0
6
0
Order By: Relevance
“…This unique mechanism overcomes the issues of hypoxia and the limited depth of penetration of light in PDT. 86 Although CDT as a widely used ROS-mediated therapeutic strategy holds promise for cancer treatment, there are still several challenges that need to be addressed. Generally, an effective Fenton reaction requires a strong acidic environment (pH = 3−4), while the pH value of tumor tissues is approximately 6.5, resulting in a lower efficiency of CDT.…”
Section: Combined Ptt-cdtmentioning
confidence: 99%
See 1 more Smart Citation
“…This unique mechanism overcomes the issues of hypoxia and the limited depth of penetration of light in PDT. 86 Although CDT as a widely used ROS-mediated therapeutic strategy holds promise for cancer treatment, there are still several challenges that need to be addressed. Generally, an effective Fenton reaction requires a strong acidic environment (pH = 3−4), while the pH value of tumor tissues is approximately 6.5, resulting in a lower efficiency of CDT.…”
Section: Combined Ptt-cdtmentioning
confidence: 99%
“…It is well-known that CDT relies on the reaction of H 2 O 2 with Fenton/Fenton-like catalysts to generate ·OH, without the need for O 2 or external energy input. This unique mechanism overcomes the issues of hypoxia and the limited depth of penetration of light in PDT . Although CDT as a widely used ROS-mediated therapeutic strategy holds promise for cancer treatment, there are still several challenges that need to be addressed.…”
Section: Cu-mediated Combined Cancer Therapymentioning
confidence: 99%
“…Much of PDT-related research is focused on the development of novel agents for improved tumor specificity. This can be achieved through two approaches. First, the modification of photosensitizers with biological conjugates, such as peptide or antibody conjugates, facilitates targeted delivery specifically to tumors .…”
Section: Introductionmentioning
confidence: 99%
“…This increases the efficacy of immunotherapy ( Wang-Bishop et al, 2020 ) in patients who had minimal benefited from initial clinical treatment. Importantly, extensive studies have shown that traditional therapies, such as chemotherapy ( Fabian et al, 2021 ; Kodumudi et al, 2010 ), targeted therapy, radiotherapy (RT) ( Huang et al, 2021 ; Vaes et al, 2021 ), and photodynamic therapy (PDT) ( Yu et al, 2023 ) can function as ICD inducers to activate the host-reactive immune response ( Rodriguez-Ruiz et al, 2020 ; Zhu et al, 2021 ), although they were originally acknowledged to directly kill tumor cells ( Cherniavsky et al, 2015 ). Notably, only a limited number of these traditional regimens serve as ICD inducers or induce sufficient ICD ( Fu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%